Effects of vortex structure on performance characteristics of a multiblade fan with inclined tongue. (December 2019) - Lun, Yuxin; Lin, Limin; He, Haijiang; Ye, Xinxue; Zhu, Zuchao; Wei, Yikun
The effects of complex vortex structure on the internal flow and performance of a centrifugal fan with inclining symmetrical volute tongue were investigated by numerical simulations. The comparison between experimental results and numerical results on performance of a centrifugal fan is presented. To provide a quantitative analysis on the vortex structure in the internal flow of fan, Q criterion as a rule of vortex decision is implemented. Effects on vortex structure and X-velocity of the volute outlet are analyzed by modifying clearance and radius. It is analyzed to provide insight into the performance of the centrifugal fan. Special attention is devoted to the influence of the static pressure and efficiency of the fan by increasing radius of the volute tongue, changing tongue clearance and inclining volute tongue in this paper. The results also show that the static pressure of model B rises as much as 10.59 Pa and the efficiency can be improved by more than 4% compared with the original configuration due to the reduction of flow loss. It is further found that the static pressure efficiency increases with decreasing Q value distribution in the internal flow of the fan.